2012
DOI: 10.1037/a0025869
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and partner violence among urban women seeking emergency care.

Abstract: Growing evidence suggests intimate partner violence (IPV) and substance misuse are co-occurring problems that disproportionately affect low income urban women seeking care in emergency departments (EDs) and represent leading causes of injuries that result in ED visits. This paper examines temporal bi-directional associations between different types of drug and alcohol use and different types of IPV in a longitudinal study of a representative sample of 241 low income, urban women receiving emergency care from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 65 publications
3
98
1
2
Order By: Relevance
“…[25][26][27] Research has demonstrated the significant impact of IPV on women's health behaviors during pregnancy, including higher rates of smoking, 11,28 alcohol use, and substance use. [29][30][31] Inadequate weight gain, smoking, alcohol use, and substance use are well-established risk factors for adverse neonatal outcomes and will be discussed in greater detail below.…”
Section: Health Behaviorsmentioning
confidence: 99%
“…[25][26][27] Research has demonstrated the significant impact of IPV on women's health behaviors during pregnancy, including higher rates of smoking, 11,28 alcohol use, and substance use. [29][30][31] Inadequate weight gain, smoking, alcohol use, and substance use are well-established risk factors for adverse neonatal outcomes and will be discussed in greater detail below.…”
Section: Health Behaviorsmentioning
confidence: 99%
“…Unique factors identified with IPV and drug use, specifically, included potential dependence on partners for drug supply, coerced sexual behavior to obtain drugs as well as low status of drug-using women, which could further impede negotiation of condom use by partners. Despite substantial research indicating significantly higher prevalence of all types and severity of IPV victimization among drug or alcohol dependent women and bidirectional associations between using different types of drugs and alcohol and IPV victimization, 7,26 the availability and use of effective screening, brief interventions and coordinated systems of care to address these co-occurring problems in health care settings remain very limited. Although several IPV screening tools for women in health care settings have been evaluated and validated over the past decade, to our knowledge, only one IPV screening tool (the Jellinek Inventory for assessing Partner Violence [J-IPV] scale) has been validated with drug dependent women in a drug treatment setting.…”
Section: Ipv and Suds: Mental And Physical Health Comorbiditiesmentioning
confidence: 99%
“…27 Because the majority of women with SUDs never receive substance abuse treatment, it is important to extend the reach of IPV screening and brief interventions that target women with SUDS to health care settings where women with SUDs are more likely to receive services. Given the disproportionately large number of women with SUDs who receive emergency care services for injuries or medical or psychiatric problems related to IPV, 26 it is particularly important to introduce routine screening for IPV among women with SUDs in emergency care settings. Scaling routine screening for IPV in emergency care settings may significantly increase the identification of women with SUDs at risk of IPV and link them to appropriate IPV services and substance abuse treatment.…”
Section: Ipv and Suds: Mental And Physical Health Comorbiditiesmentioning
confidence: 99%
“…Analizando los tipos de drogas comúnmente involucrados en el contexto de la violencia doméstica, algunos estudios han destacado la proliferación del consumo de cocaína, tanto esnifada como en base 11 , al contrario de lo que sucede en otros, en los cuales el consumo de cannabis es el que mantiene una mayor asociación con la victimización familiar 12 . Sin embargo, revisando este problema podemos observar que el consumo de alcohol es la sustancia más tradicionalmente ligada con los agresores por delitos de violencia de género, tanto en nuestro país como en otros 13,14 .…”
Section: Introductionunclassified